Pemanfaatan Waktu Luang Era Pandemi Covid-19 melalui Kegiatan Bimbingan Keagamaan - Afiati, Gita Puspita (Khidmat, 2021)
Currently, all countries are still stricken by disasters caused by the Covid-19 virus. This epidemic has had an impact on the world of education, including Islamic religious education learning activities. In conditions like this, Islamic religious education learning still has a very important role for the community, especially students when facing a pandemic. In essence, the purpose of learning Islamic religious education is to increase the faith, understanding, appreciation and experience of students about the religion of Islam, so that they become human beings who believe and fear Allah and have noble character in personal, social, national and state life. This study uses a field method with direct observation at the service location through activities at the madrasah diniyah and recitation of the ta'lim majlis in Cijeungjing Village. To overcome various learning problems at the madrasah diniyah and recitation of the ta'lim majlis in Warungjati Hamlet, Cijeungjing Village, solutions and alternative teaching assistance activities are offered on a regular and scheduled basis at the two religious education institutions.